HAND BONE DENSITOMETRY AND BIOCHEMICAL MARKERS OF BONE TURNOVER IN RHEUMATOID ARTHRITIS - Sabire Akın; Oya Güleç; Mehmet Beyazova; Feza Korkusuz (Archives of Rheumatology, 2004)
Objective: The aim of this study was to assess hand bone mineral status with bone mineral densitometry (BMD) and biochemical markers such as osteocalcin (OC) and N-telopeptides (NTX) in women with rheumatoid arthritis (RA) and healthy controls. Materials and methods: Forthy-one female patients with RA [pre-menopausal (pre-RA) n=20; post-menopausal (post-RA) n=21) ] and 50 healthy controls [ pre-menopausal (pre-CON) n=26; post-menopausal (post-CON) n=24] were studied. Hand BMD was measured with dual energy x-ray absorptiometry (DEXA). Results: Hand BMD values were significantly lower in the pre-RA patients than the pre-CON (p=0.002) but there was no difference betweeen post-RA and post-CON subjects (p>0.05). Hand BMD values were significantly reduced in the post-CON subjects when compared with the pre-CON subjects (p=0.001). In RA patients the difference between pre-RA and post-RA was not significant (p>0.05). Serum OC and NTX values did not show any significant difference among groups (p>0.05). Conclusion: Results indicated that significant decrease in hand BMD in the patients with RA is present during the earlier years of the disease but later the situation becomes similar to age and sex matched controls. Hand BMD measurement by DEXA proves to be a useful indicator of periarticular bone loss. The earlier use of DMARDs may be beneficial in preventing bone loss and bone destruction by retarding disease progression.